2020
DOI: 10.3390/cryst10030167
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Zn-Doped Al-Rich Alloys for Fast on-Board Hydrogen Production

Abstract: For the purpose of investigating the effect of Zn replacement of In3Sn on the hydrogen production performance of Al-rich alloy ingots, Al-Ga-In3Sn alloys with various Zn dosages (0–5 wt.%) were prepared by a traditional melting and casting technique. The phase compositions and microstructures were characterized using X-ray diffractometer (XRD) and scanning electron microscope (SEM) with an Energy Dispersed X-ray system (EDS). The SEM results indicate that, with a small amount of Zn instead of In3Sn, the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, a notable obstacle hindering the practical application of the aluminum hydrolysis process is the inert aluminum oxide layer that naturally forms on the surface of pure aluminum, impeding the hydrogen generation process. Various techniques have been examined to remove the passive oxide, including mechanical activation of Al [ 22 , 23 , 24 ], liquid metal activation and alloying [ 25 , 26 , 27 ], activation of Al in alkaline or acidic solutions [ 28 , 29 , 30 ], activation by Al 2 O 3 or Al(OH) 3 [ 31 , 32 , 33 ], activation with carbon-based materials [ 34 , 35 , 36 ], and others [ 37 , 38 , 39 , 40 ]. Significant improvements were achieved using these methods, mostly related to aluminum–water reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…However, a notable obstacle hindering the practical application of the aluminum hydrolysis process is the inert aluminum oxide layer that naturally forms on the surface of pure aluminum, impeding the hydrogen generation process. Various techniques have been examined to remove the passive oxide, including mechanical activation of Al [ 22 , 23 , 24 ], liquid metal activation and alloying [ 25 , 26 , 27 ], activation of Al in alkaline or acidic solutions [ 28 , 29 , 30 ], activation by Al 2 O 3 or Al(OH) 3 [ 31 , 32 , 33 ], activation with carbon-based materials [ 34 , 35 , 36 ], and others [ 37 , 38 , 39 , 40 ]. Significant improvements were achieved using these methods, mostly related to aluminum–water reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…In the last article, Qian Gao et al [10] present an experimental study on Zn-doped Al-rich alloys for fast on-board hydrogen production. The hypothesis that Zn will change the hydrogen production performance of the alloy by entering the GB phase was verified and it was found that the reaction mechanism cannot only be explained by the eutectic reaction of the GB phase and Al.…”
mentioning
confidence: 99%